The Effect of Carbon Nanotubes on Microstructure and Mechanical Properties of Al/TiH2/CNT Foam Precursor Produced via Continual Annealing and Roll-Bonding Process - Qasemi, Maryam; Habibolahzadeh, Ali (Journal of Composites and Compounds, 2025)
The most important issue that should be considered in the reinforcement role of the carbon nanotubes in composites is uniform distribution of reinforcement particles in the composite. The unique characteristics of carbon nanotubes can have maximum efficiency by proper and uniform distribution. In many studies in this regard, various methods have been used in order to obtain a proper distribution; and in this study, accumulative roll bonding (ARB), a severe plastic deformation (SPD) process, was used. In this study, the distribution of carbon nanotube particles in aluminum matrix after eight cycles of Continual Annealing and Roll-Bonding (CAR) process was studied by using a scanning electron microscope. Also, the effect of the distribution of reinforcement particles on tension strength and hardness of Al/TiH2/CNT foam precursor was investigated. Keywords: Carbon nanotubes, Metal foam composite, Accumulative Roll Bounding, Microstructure, Mechanical properties.